Pengembangan Media Pembelajaran Android - Based Physics Laboratory Untuk Meningkatkan Kompetensi Peserta Didik Materi Radiasi Benda Hitam - S.Pd., M.Pd.I, Subkannayla (Inovasi: Jurnal Diklat Keagamaan, 2022)
Learning physics through the development of learning media with the android based physics laboratory is expected to increase the competence of students in the black body radiation material. This research is a development research (Research and Development. The results of the analysis obtained as many as 73% of students think that the development of learning media Android Based Physics Laboratory is very effectively used for learning black body radiation and 26% of students think that learning media Android Based Physics Laboratory is learning which is creative and interactive as well as an additional supplement in the teaching and learning process. The test given to students shows a significant increase in learning outcomes. These indicators can be seen from the average Pre-Test score of 49.67 to 80.64 in the Post-Test. The value of t count < t table, this shows that the Android Based Physics Laboratory learning media can improve student learning outcomes.P Value is smaller than alpha 5% (0.05), meaning that there is a significant difference between learning outcomes before and after the application of your learning media roid Based Physics Laboratory. The distribution of the skill scores of students is in the range between 80 to 90, this shows that learning activities with android based physics laboratory media have a good impact on students.